You are not a doll, not a commodity! – Contemporary Ukrainian Advice Literature for Girls - Świetlicki, Mateusz (Slavia Occidentalis, 2016)
The author of the article focuses on the stereotypical depiction of femininity in contemporary Ukrainian advice literature. By discussing norms and patterns of behavior present in Ukrainian advice literature for girls, he shows their role in the post-Soviet reemergence of patriarchal norms. The article focuses on five books published in the last five years: A Real Lady. A Handbook for Girls (2012), A Book for a Young Lady (2014), A 100% Girl (2016), Encyclopedia for Girls (2016), and A Stylish Book for a Little Lady (2015).